Advanced Membrane Systems for Tissue Engineering - Salerno, Simona; Morelli, Sabrina; De Bartolo, Loredana (Current Organic Chemistry, 2017)
Background: In tissue engineering applications, advanced membrane systems provide useful and adaptable biomimetic microenvironment able to sustain cell viability and functions, enabling the delivery and diffusion of biochemical factors, cell nutrients, and products, and mimicking the natural biological extracellular matrix. Proper cell-material interactions favour cell adhesion and trigger cell growth, migration, proliferation, differentiation and functional activation. The wide availability of biocompatible polymers offers the possibility to develop membranes with tuned morphological, physico-chemical, mechanical and transport properties for targeted tissues. Objective: In this review, an in-depth examination of how the membrane properties are able to influence and direct the cellular morpho-functional behaviour of specific engineered tissues is discussed. Furthermore, an overview of the advanced membrane systems, in different configuration and composition, for the biofabrication of tissues and organs is reported.
Keywords: Polymeric membranes